Altered function of intracortical networks in chronic lateral epicondylalgia. (12th February 2016) - Burns, E.; Chipchase, L.S.; Schabrun, S.M.
Abstract: Background: Lateral epicondylalgia (LE) is a musculotendinous condition characterized by persistent pain, sensorimotor dysfunction and motor cortex reorganization. Although there is evidence linking cortical reorganization with clinical symptoms in LE, the mechanisms underpinning these changes are unknown. Here we investigated activity in motor cortical (M1) intracortical inhibitory and facilitatory networks in individuals with chronic LE and healthy controls. Methods: Surface electromyography was recorded bilaterally from the extensor carpi radialis brevis (ECRB) muscle of 14 LE (4 men, 41.5 ± 9.9 years) and 14 control participants (4 men, 42.1 ± 11.1 years). Transcranial magnetic stimulation of M1 was used to evaluate resting and active motor threshold, corticomotor output, short‐ (SICI) and long‐latency intracortical inhibition (LICI) and intracortical facilitation (ICF) of both hemispheres. Results: In individuals with LE, SICI ( p  = 0.005), ICF ( p  = 0.026) and LICI ( p  = 0.046) were less in the M1 contralateral to the affected ECRB muscle compared with healthy controls. Motor cortical threshold (rest: p  = 0.57, active: p  = 0.97) and corticomotor output ( p  = 0.15) were similar between groups. No differences were observed between individuals with LE and healthy controls for the M1 contralateral to the unaffected ECRB muscle. Conclusions: These data provide evidence of less intracortical inhibition mediated by both GABAA and GABAB receptors, and less intracortical facilitation in the M1 contralateral to the affected ECRB in individuals with LE compared with healthy controls. Similar changes were not present in the M1 contralateral to the unaffected ECRB. These changes may provide the substrate for M1 reorganization in chronic LE and could provide a target for future therapy. What does this study add: Lateral epicondylalgia (LE) is a common musculoskeletal condition characterized by elbow pain and sensorimotor dysfunction. The excitability and organization of the motor cortical representation of the wrist extensor muscles is altered in LE, but the mechanisms that underpin these changes are unknown. evidence of less intracortical inhibition mediated by both GABAA and GABAB receptors, and less intracortical facilitation mediated by NMDA receptors, in the M1 contralateral to the affected extensor carpi radialis brevis muscle in chronic LE compared with healthy controls. Altered activity in intracortical networks may contribute to altered motor cortex organization in LE and could provide a potential target for future treatments.